ESTUDIO SOBRE EL NIVEL DE SATISFACCIÓN DE LA CIUDADANÍA DEL SERVICIO DE AGUA POTABLE POR EL GOBIERNO AUTÓNOMO DESCENTRALIZADO CANTONAL DE SARAGURO EN EL AÑO 2012 - Erreyes Armijos, Martha Enidh. (2016)
he purpose of this research work is to determine the level of citizen satisfaction with the service they received from Drinking Water in the urban part by the Public Company called EMAPASA in 2012 which currently remains therefore in this process research is able to determine the reasons why there is dissatisfaction beneficiary; and it was established that there are causes like winter , budget, material management , including water quality , as the main causes that lead them poor provision of drinking water . In addition the Company as such carries a delivery process for provisioning the service it does not cover the requirements required by the beneficiaries citizens also verified that do not have a Land Use Plan for the supply of drinking water in the urban part in 2012 , this in order to know what is the system of transfer of water to the water treatment plant under this scheme is determined that there are faults that aggravate the problems over the rejection of certain local communities to the administration of this service. The main purpose of this paper is to propose a future Improvement Plan on drinking water service in the urban part of the Canton Saraguro, to help combat the shortcomings observed improve service quality and thus meet and provide quality service to the citizens beneficiaries Drinking Water.